2022
DOI: 10.3389/fmicb.2022.1037467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms involved in tissue-specific metabolic modulation by SARS-CoV-2

Abstract: Coronavirus disease 2019 (COVID-19) is triggered by the SARS-CoV-2, which is able to infect and cause dysfunction not only in lungs, but also in multiple organs, including central nervous system, skeletal muscle, kidneys, heart, liver, and intestine. Several metabolic disturbances are associated with cell damage or tissue injury, but the mechanisms involved are not yet fully elucidated. Some potential mechanisms involved in the COVID-19-induced tissue dysfunction are proposed, such as: (a) High expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 242 publications
0
4
0
Order By: Relevance
“…Therefore, inflammatory factors play an important role in inhibition of IBV infections ( Zhang et al., 2021 ). The SARS-CoV infection is known to increase the expressions of inflammatory factors, including IL-1, IL-6, and IL-8, and IBV is similar ( Dos Santos et al., 2022 ). Studies have shown that IBV infection is followed by a significant upregulation of the body's inflammatory factors, including IL-1, IL-6, IL-1β, TNF-α, and MIP-1β ( Xiao et al., 2008 ; Liao et al., 2011 ; Dar et al., 2014 ; Zhu et al., 2021 ; Tang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammatory factors play an important role in inhibition of IBV infections ( Zhang et al., 2021 ). The SARS-CoV infection is known to increase the expressions of inflammatory factors, including IL-1, IL-6, and IL-8, and IBV is similar ( Dos Santos et al., 2022 ). Studies have shown that IBV infection is followed by a significant upregulation of the body's inflammatory factors, including IL-1, IL-6, IL-1β, TNF-α, and MIP-1β ( Xiao et al., 2008 ; Liao et al., 2011 ; Dar et al., 2014 ; Zhu et al., 2021 ; Tang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 may also infect skeletal muscle (Disser et al 2020 ; Santos et al 2022 ), causing musculoskeletal and pain-related symptoms (Mao et al 2020 ). Among these symptoms are fatigue (38%–85%), weakness (approx.…”
Section: Covid-19 Symptoms and Their Relation With Chronic Painmentioning
confidence: 99%
“…[9][10][11][12] In addition, the process of abscess formation may also present a pathophysiological state called a "cytokine storm". 11,13 For example, inflammatory cytokines such as interleukin-10 (IL-10) can induce abscess formation through the mitogen-activated protein kinase (MAPK) pathway. 14 Interleukin-4 (IL-4) can antagonise the effects of IL-10 during infection, 15 attenuate the inflammatory response and promote repair of necrotic tissue by promoting alternative activation of macrophages.…”
Section: Introductionmentioning
confidence: 99%